Network-based transcranial direct current stimulation enhances attention function in healthy young adults: a preliminary study - Wei, Xiaoyu; Zhou, Rong; Zheng, Suwang; Zhang, Yufeng; Feng, Xiaofan; Lü, Jiaojiao (Frontiers in Human Neuroscience, 2024)
Purpose: Attention, a complex cognitive process, is linked to the functional activities of the brain's dorsal attention network (DAN) and default network (DN). This study aimed to investigate the feasibility, safety, and blinding efficacy of a transcranial direct current stimulation (tDCS) paradigm designed to increase the excitability of the DAN while inhibiting the DN (DAN+/DN-tDCS) on attention function in healthy young adults.In this randomized controlled experiment, participants were assigned to either the DAN+/DN-tDCS group or a sham group. A single intervention session was conducted at a total intensity of 4 mA for 20 min. Participants completed the Attention Network Test (ANT) immediately before and after stimulation. Blinding efficacy and adverse effects were assessed post-stimulation.Results: Forty participants completed the study, with 20 in each group. Paired-sample t-test showed a significant post-stimulation improvement in executive effect performance (t=2.245; p=0.037) in the DAN+/DN-tDCS group. The sham group did not exhibit any significant differences in ANT performance. Participants identified the stimulation type with 52.50% accuracy, indicating no difference in blinding efficacy between groups (p=0.241). Mild-to-moderate adverse effects, such as stinging, itching, and skin reddening, were reported in the DAN+/DN-tDCS group (p<0.05).: DAN+/DN-tDCS enhanced attention function in healthy young individuals, particularly in improving executive effect performance. This study presents novel strategies for enhancing attentional performance and encourages further investigation into the mechanisms and outcomes of these interventions across diverse populations.